Management of Necrotising Fasciitis (Baqai Journal of Health Sciences)
Necrotising fasciitis is an uncommon condition characterised by extensive toss of skin fascia and subcutaneous tissues with sparing of underlying muscles. Mortality of this group of patients is quite high. It is a case study of nine patients who presented to us with necrotising fasciitis at the site of intra-muscular or intra-venous injection caused by use of unsterile or dirty syringe. Infection is usually of poly-microbial drug resistant organisms. Fasciotomy and surgical debridment was done in these cases under antibiotic cover but antibiotics failed to prove as effective mode of treatment